Answer:
YES
Step-by-step explanation:
4(3b-4)=2(6b-8)
12b-16=12b-16
YES
Answer:
B. - 4x - 5
Step-by-step explanation:
(p о n) (x) is the same thing as (p(n(x))
We know n(x) = x - 5, so let's input that into our expression
(p(x - 5))
Since we know p(x) = x^2 + 6x, let's replace the x with the new value x-5. Now our expression is:
p(x) = (x - 5)^2 + 6(x - 5)
Now all we have to do is simplify.
(x - 5)^2 is the same as: (x - 5)(x - 5)
Using the foil method, it simplifies to: x^2 - 10x + 25
6 (x - 5) = 6x - 30
Now our expression is: x^2 - 10x + 25 + 6x - 30
Combine like terms: x^2 - 4x - 5
The expression is: - 4x - 5
Add the three angles and set them to 180
4x-13+15+x+18=180
5x+20=180
5x=160
x=32
Then plug in to get A and C
A=4*32-13
A=115
C=32+18
C=50
Answer:
15.64 Step-by-step explanation: I used a calculator
If you mean (4.9*10^-2) times (9.80<span>*10^2) then the product is 4.802*10^1 in </span>scientific notation<span>.</span>